Immunogenic characterization of the chimeric surface antigen 1 and 2 (SAG1/2) of Toxoplasma gondii expressed in the yeast Pichia pastoris - Lau, Yee Ling; Thiruvengadam, Girija; Lee, Wei Wei; Fong, Mun Yik (Springer Verlag (Germany), 2011)
In this study, we successfully expressed a chimerical surface antigen 1 and 2 (SAG1/2) of Toxoplasma gondii in Pichia pastoris. Eighty human serum samples, including 60 from confirmed cases of toxoplasmosis, were tested against the purified recombinant SAG1/2 in Western blots. Results of Western blots targeted at Toxoplasma IgG and IgM showed that the recombinant SAG1/2 reacted with all sera from the toxoplasmosis cases but none with the Toxoplasma-negative serum samples. These results showed that the P. pastoris-derived recombinant SAG1/2 was sensitive and specific and suitable for use as antigen for detecting anti-Toxoplasma antibodies. To further investigate the immunological characteristic of the recombinant protein, the recombinant SAG1/2 was injected subcutaneously into BALB/c mice, and their serum was tested against total protein lysate of T. gondii. Mice immunized with the recombinant SAG1/2 reacted specifically with the native SAG1 and SAG2 of T. gondii. Significant proliferation of splenocytes stimulated with tachyzoite total protein lysate was observed in vaccinated BALB/c mice but not in those from negative control mice. Specific production of IFN-gamma, the Th1-type cytokines, was also found in stimulated splenocytes from vaccinated mice. These results show that the chimeric protein recombinant SAG1/2 can elicit a Th1-associated protection against T. gondii infections in mice. Finally, vaccinated mice were significantly protected against lethal challenge with live T. gondii RH strain tachyzoites (P < 0.005), and their survival time increased significantly compared to the negative control.